Resin-based hard carbon material, preparation method thereof and battery

By regulating the crosslinking degree of phenolic resin and the growth of the microcrystalline lateral length La, resin-based hard carbon material with closed-pore structure is solved, the problem of open pore structure of existing resin-based hard carbon material is improved, and its sodium storage capacity and electrochemical performance are suitable for the industrial production of sodium ion batteries.

CN119735193AActive Publication Date: 2025-04-01HUNAN SHINZOOM TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411935417.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Most of the existing resin-based hard carbon materials have open pore structures, making it difficult to increase their reversible sodium storage capacity.

Method used

By a preparation method, including the first and second curing treatments of the hard carbon precursor material, pre-carbonization and high-temperature carbonization, the degree of crosslinking of the phenolic resin and the growth of the transverse length La of the microcrystals are regulated to form a rich closed-cell structure.

Benefits of technology

High-capacity resin-based hard carbon material is obtained, which improves its electrochemical performance, is suitable for sodium ion batteries, and is simple in preparation, with a wide range of raw materials, and is cheap in price, suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211395390000131
    Figure BDA0005211395390000131
  • Figure BDA0005211395390000151
    Figure BDA0005211395390000151
  • Figure BDA0005211395390000161
    Figure BDA0005211395390000161
Patent Text Reader

Abstract

The invention provides a resin-based hard carbon material, a preparation method thereof and a battery. The preparation method comprises the following steps: carrying out first curing treatment and second curing treatment on a hard carbon precursor material to obtain a cured resin product; sequentially carrying out pre-carbonization and high-temperature carbonization in a protective atmosphere to obtain the resin-based hard carbon material with a closed-pore structure; wherein the hard carbon precursor material comprises phenolic resin and a curing agent. According to the preparation method provided by the invention, the high-capacity resin-based hard carbon material with a rich closed-pore structure is obtained, meanwhile, the preparation method is simple, a complicated treatment process is not needed, and the raw materials are wide in source, low in price, stable in property and more suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and relates to a resin-based hard carbon material, a preparation method thereof, and a battery, and in particular to a resin-based hard carbon material more suitable for sodium ion batteries, a preparation method thereof, and a sodium ion battery. Background Art

[0002] As an important battery material, hard carbon anode has many significant advantages. It has excellent sodium storage capacity. The material per unit mass can store more sodium ions, thereby improving the energy density and endurance of the battery. From the perspective of the sodium storage mechanism of hard carbon anode, different types of pore structures in hard carbon materials have an important influence on the electrochemical performance of sodium ion batteries. Among them, hard carbon materials with closed pore structures are more conducive to the formation of sodium clusters in characteristic pores during sodium storage, thereby providing high specific capacity and affecting the intercalation and filling process of sodium ions. As the content of closed pore structure increases, the number of sodium ion storage sites increases, and the specific surface area of ​​hard carbon also decreases accordingly. This structural characteristic can significantly improve the low-voltage platform capacity, initial coulombic efficiency and cycle stability of hard carbon anode.

[0003] The hard carbon negative electrodes on the market today can be divided into biomass-based, resin-based, asphalt-based and anthracite-based types. Resins have the advantages of high carbon yield and good product consistency and are widely used in the manufacture of hard carbon. However, most of the resin-based hard carbons currently obtained have an open pore structure, which is not conducive to the improvement of the reversible sodium storage capacity of hard carbon materials.

[0004] Therefore, how to obtain resin-based hard carbon with rich closed-pore structure is a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a resin-based hard carbon material and a preparation method thereof and a battery. The preparation method provided by the present invention obtains a high-capacity resin-based hard carbon material with a rich closed-cell structure. At the same time, the preparation method is simple, does not require a complicated processing process, and the raw material source is wide, the price is low, and the properties are stable, which is more suitable for industrial production.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a resin-based hard carbon material, the preparation method comprising the following steps:

[0008] Performing a first curing treatment and a second curing treatment on the hard carbon precursor material to obtain a cured resin product;

[0009] Under a protective atmosphere, pre-carbonization and high-temperature carbonization are sequentially performed to obtain a resin-based hard carbon material with a closed-pore structure;

[0010] Wherein, the hard carbon precursor material includes phenolic resin and a curing agent.

[0011] It should be noted that the present invention does not specifically limit the specific types of phenolic resins. The present invention is applicable to any conventional types of phenolic resins that can be used for preparing hard carbon, for example, it can be at least one of phenol-formaldehyde resin, m-diphenol-formaldehyde resin, p-diphenol-formaldehyde resin or phenol-furfural resin.

[0012] The preparation method provided by the present invention coordinates the raw materials, preparation process, preparation sequence and reaction atmosphere to regulate the cross-linking degree of the phenolic resin and the growth process of the microstructure of the lateral length La of the crystallites closely related to the closed pores of the material during the pre-carbonization process, which is beneficial to the formation of closed pores in the hard carbon material, thereby obtaining a high-capacity resin-based hard carbon material; at the same time, the preparation process does not involve synthetic reactions and complex equipment, and the raw materials are widely available, low-priced, and stable in nature, making it more suitable for industrial production.

[0013] In the present invention, the first curing process realizes the preliminary cross-linking of the curing agent and the phenolic resin, which can effectively avoid the uneven pores of various parts of the material caused by the large amount of gas escaping during curing, resulting in the expansion of the resin block and affecting the hardness and density of the material; the second curing process realizes the control of the cross-linking process of the phenolic resin, so that the resin has a higher degree of cross-linking, which is beneficial to the regulation of the lateral length La of the crystallites in the microstructure in the subsequent pre-carbonization process, avoiding the softening and agglomeration of the material in the subsequent pre-carbonization treatment stage, thereby affecting the subsequent formation of closed pores, and ultimately affecting the pore size and quantity and electrochemical properties of the hard carbon product.

[0014] The present invention performs pre-carbonization treatment under a protective atmosphere, thereby reducing the oxygen content of the obtained product, which promotes the migration and rearrangement of carbon atoms in the subsequent carbonization process; it also realizes the effective regulation of the growth process of the microstructure of the microcrystal lateral length La which is closely related to the closed pore, so that the carbon layer with a longer La can better develop into a closed pore structure; the long La is beneficial to the formation of closed pores in the hard carbon, thereby leading to the improvement of the electrochemical performance, and different pre-carbonization temperatures can reduce the oxygen content by changing the connection form between molecules, thereby greatly promoting the growth of the microscopic lateral length La related to the closed pore in the carbonization process, and accelerating the formation of the closed pore structure.

[0015] In the present invention, raw materials, preparation process, preparation order and reaction atmosphere are all indispensable and work together to achieve the purpose of obtaining a hard carbon material with a closed-pore structure. If there is no curing agent in the hard carbon precursor material, this non-cross-linked linear molecular structure will cause uncontrollable foaming and expansion of the material during the carbonization process, which not only affects the performance of the material, but also makes it impossible to control its structure in the subsequent treatment process due to this disordered state, thereby affecting the physical indicators and electrochemical properties. If other atmospheres, such as an etching atmosphere, are used during the pre-carbonization process, they will react with the material, increase the specific surface area, and destroy the pore structure, and similarly, no hard carbon with a suitable closed-pore structure can be obtained.

[0016] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0017] Preferably, the mass proportion of the curing agent in the hard carbon precursor material is 8% to 12%, for example 8%, 8.5%, 10%, 11.5% or 12%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] In the present invention, the mass proportion of the curing agent in the hard carbon precursor material is 8% to 12%, so that the effects of the subsequent first curing treatment and the second curing treatment are better exerted.

[0019] Preferably, the curing agent includes any one of hexamethylenetetramine, paraformaldehyde, A-stage thermosetting phenolic aldehyde or furfural, or a combination of at least two thereof, preferably hexamethylenetetramine.

[0020] In the present invention, except for hexamethylenetetramine, the other types of curing agents can be curing agents that generate aldehyde groups or curing agents containing aldehyde group compounds.

[0021] The present invention selects hexamethylenetetramine as a curing agent, which is decomposed in the first curing treatment process to form dimethanolamine and formaldehyde, thereby being cross-linked with the phenolic resin, and can effectively avoid the uneven pores of various parts of the material caused by the escape of a large amount of gas during curing, resulting in the expansion of the resin block and affecting the hardness and density of the material; and in the second curing treatment process, di(hydroxybenzyl)amine and tri(hydroxybenzyl)amine are mainly generated, thereby achieving effective regulation of the cross-linking degree of the resin and obtaining a resin block with better thermal stability.

[0022] Preferably, the temperature of the first curing process is lower than the temperature of the second curing process.

[0023] Preferably, the temperature of the first curing treatment is 100-120°C, such as 100°C, 105°C, 110°C, 115°C or 120°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Preferably, the time of the first curing treatment is 1 to 5 hours, such as 1 hour, 2 hours, 3 hours, 4 hours or 5 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, the temperature of the second curing treatment is 120-180°C, for example, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C or 180°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In the present invention, by regulating the temperature of the first curing treatment to be 100-120°C and / or the temperature of the second curing treatment to be 120-180°C, the temperature of the first curing treatment can effectively avoid the uneven porosity of various parts of the material caused by the large amount of gas released during curing, that is, avoiding the simultaneous crosslinking and degassing; the temperature of the second curing treatment avoids excessive decomposition of the curing agent. For example, when the curing agent is hexamethylenetetramine, the temperature is greater than 180°C, which will react with free phenol to release NH3 and form methylene bonds, thereby affecting the migration and rearrangement of carbon atoms during the pyrolysis process during the pre-carbonization process.

[0027] Preferably, the time of the second curing treatment is 4 to 8 hours, for example 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] Preferably, the product after the second solidification treatment is crushed, and the mesh size of the crushing treatment is 100 mesh to 325 mesh, for example, 100 mesh, 125 mesh, 150 mesh, 175 mesh, 200 mesh, 225 mesh, 250 mesh, 275 mesh, 300 mesh or 325 mesh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In the present invention, the cured resin block is crushed into 100-325 meshes, which is more conducive to the regulation of particle size during pre-carbonization. The smaller the particles in the pre-carbonization stage, the more thorough the carbonization, the better the development of the lateral length La of the microcrystals with larger lateral length, and the higher the capacity of the hard carbon material after subsequent carbonization.

[0030] Preferably, in the product obtained by the pre-carbonization, the lateral length La of the crystallite is 7 to 15 nm, for example, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm, 10 nm, 10.5 nm, 11 nm, 11.5 nm, 12 nm, 12.5 nm, 13 nm, 13.5 nm, 14 nm, 14.5 nm or 15 nm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, in the product obtained by the pre-carbonization, the mass proportion of oxygen element is 3% to 10%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] In the present invention, the lateral length La of the crystallites of the product after further pre-carbonization is 7 to 15 nm and / or the mass proportion of oxygen element is 3% to 10%, which can better promote the formation of closed pores.

[0033] Preferably, the pre-carbonization temperature is 300-800°C, for example 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In the present invention, the pre-carbonization process at 300-800° C. under a protective atmosphere can effectively control the lateral length La of the microcrystal and the mass ratio of the oxygen element.

[0035] Preferably, the pre-carbonization time is 2 to 8 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] Preferably, the high temperature carbonization temperature is 1100-1600°C, for example, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or 1600°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the high temperature carbonization time is 2 to 8 hours, for example 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] As a preferred technical solution, the preparation method comprises the following steps:

[0039] The hard carbon precursor material is sequentially subjected to a first curing treatment at 100 to 120° C. and a second curing treatment at 120 to 180° C., wherein the temperature of the first curing treatment is lower than the temperature of the second curing treatment, and the product after the second curing treatment is crushed at 100 to 325 meshes to obtain a cured resin product;

[0040] Under a protective atmosphere, pre-carbonization is performed at 300 to 800° C., and in the pre-carbonized product, the lateral length La of the microcrystal is 7 to 15 nm, and the mass proportion of the oxygen element is 3% to 10%;

[0041] The pre-carbonized product is subjected to high temperature carbonization at 1100-1600° C. to obtain a resin-based hard carbon material with a closed-cell structure;

[0042] Wherein, the hard carbon precursor material comprises phenolic resin and hexamethylenetetramine, and the mass proportion of the hexamethylenetetramine in the hard carbon precursor material is 8% to 10%.

[0043] It should also be noted that the protective atmosphere in the present invention is an atmosphere that only plays a protective role and does not participate in the reaction; for example, it can be a nitrogen atmosphere and / or an inert gas atmosphere, and the inert gas includes argon or helium.

[0044] In a second aspect, the present invention provides a resin-based hard carbon material, wherein the resin-based hard carbon material is prepared by the preparation method described in the first aspect;

[0045] The resin-based hard carbon material has a closed-pore structure inside.

[0046] In a third aspect, the present invention further provides a battery, comprising the resin-based hard carbon material as described in the second aspect.

[0047] Preferably, the battery comprises a sodium ion battery.

[0048] The resin-based hard carbon material provided by the present invention is more suitable for sodium ion batteries, and when used as a negative electrode active material, it has a more excellent effect on improving the performance of sodium ion batteries; however, in addition to sodium ion batteries, it is also possible to be used in other types of battery structures, such as lithium ion batteries, etc. The uses of conventional hard carbon materials are, in principle, applicable to the present invention.

[0049] In addition, the sodium ion battery provided by the present invention, except for the relevant characteristics of the resin-based hard carbon material defined above, the rest of the structure, preparation raw materials and preparation process are all conventional technical solutions. Those skilled in the art can make adaptive selections and adjustments based on actual needs, and the present invention will not elaborate on them.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] The preparation method provided by the present invention coordinates the raw materials, preparation process, preparation sequence and reaction atmosphere to regulate the cross-linking degree of the phenolic resin and the growth process of the microstructure of the lateral length La of the crystallites closely related to the closed pores of the material during the pre-carbonization process, which is beneficial to the formation of closed pores in the hard carbon material, thereby obtaining a high-capacity resin-based hard carbon material; at the same time, the preparation process does not involve synthetic reactions and complex equipment, and the raw materials are widely available, low-priced, and stable in nature, making it more suitable for industrial production. DETAILED DESCRIPTION

[0052] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.

[0054] In the description of this application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0055] Example 1

[0056] This embodiment provides a resin-based hard carbon material having a closed-pore structure inside the material. The preparation method of the resin-based hard carbon material is as follows:

[0057] A commercially available phenolic resin material (containing phenol-formaldehyde resin and curing agent hexamethylenetetramine, and the mass proportion of the curing agent in the commercially available phenolic resin material is 10%) is subjected to a first curing treatment at 120° C. for 5 hours, and then subjected to a second curing treatment at 180° C. for 8 hours; a resin block obtained by the curing treatment is crushed at 150 mesh to obtain a cured resin product;

[0058] Under a nitrogen atmosphere, the cured resin product was subjected to a pre-carbonization treatment at 600° C. for 2 h to obtain a pre-carbonized product;

[0059] The pre-carbonized product is subjected to high-temperature carbonization treatment at a carbonization temperature of 1600° C. under a nitrogen atmosphere to obtain the resin-based hard carbon material.

[0060] Example 2

[0061] This embodiment provides a resin-based hard carbon material having a closed-pore structure inside the material. The preparation method of the resin-based hard carbon material is as follows:

[0062] A commercially available phenolic resin material (containing phenol-formaldehyde resin and curing agent hexamethylenetetramine, and the mass proportion of the curing agent in the commercially available phenolic resin material is 8%) is subjected to a first curing treatment at 100° C. for 1 hour, and then subjected to a second curing treatment at 150° C. for 4 hours; a resin block obtained by the curing treatment is crushed at 300 mesh to obtain a cured resin product;

[0063] Under a nitrogen atmosphere, the cured resin product was subjected to a pre-carbonization treatment at 350° C. for 8 h to obtain a pre-carbonized product;

[0064] The pre-carbonized product was subjected to high-temperature carbonization treatment at a carbonization temperature of 1100° C. under a nitrogen atmosphere to obtain the resin-based hard carbon material.

[0065] Example 3

[0066] This embodiment provides a resin-based hard carbon material having a closed-pore structure inside the material. The preparation method of the resin-based hard carbon material is as follows:

[0067] A commercially available phenolic resin material (containing phenol-formaldehyde resin and curing agent hexamethylenetetramine, and the mass proportion of the curing agent in the commercially available phenolic resin material is 12%) is subjected to a first curing treatment at 110° C. for 5 hours, and then subjected to a second curing treatment at 120° C. for 8 hours; a resin block obtained by the curing treatment is crushed at 150 mesh to obtain a cured resin product;

[0068] Under a nitrogen atmosphere, the cured resin product was subjected to a pre-carbonization treatment at 800° C. for 4 h to obtain a pre-carbonized product;

[0069] The pre-carbonized product was subjected to high-temperature carbonization treatment at a carbonization temperature of 1300° C. under a nitrogen atmosphere to obtain the resin-based hard carbon material.

[0070] Example 4

[0071] The difference between this embodiment and embodiment 1 is that the curing agent in this embodiment is paraformaldehyde, and the phenolic resin is m-diphenol-formaldehyde resin.

[0072] The rest of the preparation methods and parameters were the same as those in Example 1.

[0073] Example 5

[0074] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass proportion of the curing agent in the commercially available phenolic resin material is 15%.

[0075] The rest of the preparation methods and parameters were the same as those in Example 1.

[0076] Example 6

[0077] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass proportion of the curing agent in the commercially available phenolic resin material is 5%.

[0078] The rest of the preparation methods and parameters were the same as those in Example 1.

[0079] Example 7

[0080] The difference between this embodiment and embodiment 1 is that the temperature of the first curing treatment in this embodiment is 80°C.

[0081] The rest of the preparation methods and parameters were the same as those in Example 1.

[0082] Example 8

[0083] The difference between this embodiment and embodiment 1 is that the temperature of the first curing treatment in this embodiment is 140°C.

[0084] The rest of the preparation methods and parameters were the same as those in Example 1.

[0085] Example 9

[0086] The difference between this embodiment and embodiment 1 is that the temperature of the second curing treatment in this embodiment is 200°C.

[0087] The rest of the preparation methods and parameters were the same as those in Example 1.

[0088] Example 10

[0089] The difference between this embodiment and embodiment 1 is that the pre-carbonization temperature in this embodiment is 250°C.

[0090] The rest of the preparation methods and parameters were the same as those in Example 1.

[0091] Embodiment 11

[0092] The difference between this embodiment and embodiment 1 is that the pre-carbonization temperature in this embodiment is 850°C.

[0093] The rest of the preparation methods and parameters were the same as those in Example 1.

[0094] Example 12

[0095] The difference between this embodiment and embodiment 1 is that the resin lumps obtained by the curing treatment are crushed at 40 mesh to obtain a cured resin product.

[0096] The rest of the preparation methods and parameters were the same as those in Example 1.

[0097] Comparative Example 1

[0098] The difference between this comparative example and Example 1 is that the hard carbon precursor material provided in this comparative example uses a commercially available phenolic resin that does not contain a curing agent.

[0099] The rest of the preparation methods and parameters were the same as those in Example 1.

[0100] Comparative Example 2

[0101] The difference between this comparative example and Example 1 is that the first curing treatment is not performed in this comparative example.

[0102] The rest of the preparation methods and parameters were the same as those in Example 1.

[0103] Comparative Example 3

[0104] The difference between this comparative example and Example 1 is that this comparative example does not undergo the second curing treatment.

[0105] The rest of the preparation methods and parameters were the same as those in Example 1.

[0106] Comparative Example 4

[0107] The difference between this comparative example and Example 1 is that the pre-carbonization treatment atmosphere in this comparative example is a carbon dioxide atmosphere.

[0108] The rest of the preparation methods and parameters were the same as those in Example 1.

[0109] Comparative Example 5

[0110] The difference between this comparative example and Example 1 is that this comparative example does not perform a pre-carbonization process.

[0111] The rest of the preparation methods and parameters were the same as those in Example 1.

[0112] The crystallite lateral length La and the mass ratio of oxygen element of the pre-carbonized products provided in Examples 1-12 and Comparative Examples 1-5 were characterized by the following specific characterization methods:

[0113] The crystallite lateral length (La) of the pseudo-graphite domain is calculated according to the Scherrer equation based on the X-ray diffraction (XRD) test results.

[0114]

[0115] Where K is the shape factor, usually 0.94, λ is the wavelength of the X-ray used, β is the half-peak width of the XRD peak, and θ is the diffraction angle. The XRD test results were measured by a Bruker D2 phase X-ray diffractometer with Cu Kα radiation, and an XPS spectrometer (Thermo Scientific K-Alpha, USA) was used to obtain X-ray photoelectron spectra to characterize the oxygen content.

[0116] The characterization results are shown in Table 1.

[0117] Table 1

[0118] Crystallite lateral length La (nm) Oxygen mass percentage (%) Example 1 14.8 4.2 Example 2 8.7 9.6 Example 3 13.7 3.5 Example 4 8.9 4.2 Example 5 7.4 2.2 Example 6 6.3 11.9 Example 7 15.8 2.4 Example 8 14.2 5.8 Example 9 10.4 4.8 Example 10 5.8 12.5 Embodiment 11 16.7 12.5 Example 12 13.9 4.5 Comparative Example 1 4.5 11.1 Comparative Example 2 5.9 10.8 Comparative Example 3 16.9 4.9 Comparative Example 4 17.5 5.3 Comparative Example 5 4.4 15.2

[0119] The hard carbon negative electrode materials provided in Examples 1-12 and Comparative Examples 1-5 were subjected to pore structure tests, including pore volume, pore size and specific surface area tests. The test conditions were as follows: the pore size distribution and specific surface area were measured by gas adsorption and desorption experiments. Specifically, the hard carbon materials were placed at 150°C-300°C and pressure <10 -6 Bar environment for 1h-6h; then, nitrogen / carbon dioxide is introduced at liquid nitrogen temperature to slowly return the pressure to normal pressure and then degas again for 10 -6 Bar, record the data to obtain the adsorption-desorption isotherm, and calculate the pore size distribution and pore volume data of the hard carbon negative electrode material according to the density functional theory (DFT) model. The test results are shown in Table 2.

[0120] Table 2

[0121]

[0122]

[0123] The resin-based hard carbon materials provided in Examples 1-12 and Comparative Examples 1-5 were applied to batteries and performance tests were performed.

[0124] I. Battery Preparation:

[0125] The hard carbon negative electrode materials provided in the embodiment and the comparative example were respectively mixed with the conductive agent SuperP, the binder sodium carboxymethyl cellulose and the styrene-butadiene rubber in a mass ratio of 94.5:1.5:1.5:2.5, and a proper amount of water was added to stir to form a slurry, and then the slurry was evenly coated on the current collector copper foil, and after drying, it was cut into a circular electrode with a diameter of 18 mm. Under vacuum conditions, the electrode was dried at 80°C for about 3 hours, vacuum dried at 80°C for 6 hours, and rolled to a surface density of 7 mg / cm 2The simulated battery was assembled in a glove box with an Ar atmosphere, using a metal sodium sheet as the counter electrode and 1 mol / L NaPF6 dissolved in ethylene carbonate solution as the electrolyte to form a CR2430 button battery.

[0126] II Performance Test

[0127] The prepared sodium ion battery was tested for reversible specific capacity and first coulombic efficiency: the button battery was placed in a constant temperature box of a 25°C blue electric test cabinet (T-3002A-5V 1mA) for 6 hours, and the button battery was charged and discharged at a constant current of 0.05C, with a voltage range of 0 to 2V. The discharge specific capacity of the button battery was recorded as D; the charge specific capacity was recorded as C, and the first coulombic efficiency was calculated by the following formula:

[0128] First coulombic efficiency = C / D × 100%.

[0129] The test results of the above tests are shown in Table 3.

[0130] Table 3

[0131]

[0132]

[0133] From Table 1 to Table 3, we can get:

[0134] The curing step in the present invention can significantly improve the capacity and initial efficiency of hard carbon. Specifically, the two-step curing process can avoid the foaming and expansion of the phenolic resin while ensuring the degree of cross-linking, which is beneficial to the adjustment of the pore structure in the subsequent process. At the same time, it can reduce the specific surface area of ​​the final product and improve the initial coulombic efficiency of the product.

[0135] At the same time, a series of characterizations show that pre-carbonization can reduce the oxygen content by changing the connection form between molecules, reducing the resistance to carbon atom migration and rearrangement, thereby greatly promoting the growth of La associated with closed pores in the subsequent carbonization process; however, low oxygen content easily leads to excessive growth of La, which is not conducive to increasing the number and volume of closed pores, although it helps to expand the pore size; therefore, only pre-carbonization products with appropriate La and oxygen content can obtain hard carbon materials with suitable closed pore size and pore volume, so that the obtained hard carbon materials have higher capacity and first coulombic efficiency.

[0136] In summary, the preparation method provided by the present invention, the raw materials, preparation process, preparation order and reaction atmosphere cooperate with each other to regulate the cross-linking degree of the phenolic resin and the growth process of the microstructure of the lateral length La of the crystallites closely related to the closed pores of the material during the pre-carbonization process, which is beneficial to the formation of closed pores in the hard carbon material, thereby obtaining a high-capacity resin-based hard carbon material; at the same time, the preparation process does not involve synthetic reactions and complex equipment, and the raw materials are widely available, low-priced, and stable in nature, making it more suitable for industrial production.

[0137] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a resin-based hard carbon material, characterized in that: The preparation method comprises the following steps: Performing a first curing treatment and a second curing treatment on the hard carbon precursor material to obtain a cured resin product; Under a protective atmosphere, pre-carbonization and high-temperature carbonization are sequentially performed to obtain a resin-based hard carbon material with a closed-pore structure; Wherein, the hard carbon precursor material includes phenolic resin and a curing agent.

2. The preparation method according to claim 1, characterized in that: The mass proportion of the curing agent in the hard carbon precursor material is 8% to 12%; Preferably, the curing agent includes any one of hexamethylenetetramine, paraformaldehyde, A-stage thermosetting phenolic aldehyde or furfural, or a combination of at least two thereof, preferably hexamethylenetetramine.

3. The preparation method according to claim 1 or 2, characterized in that: The temperature of the first curing process is lower than the temperature of the second curing process; Preferably, the temperature of the first curing treatment is 100-120° C., and the time of the first curing treatment is 1-5 hours; Preferably, the temperature of the second curing treatment is 120-180° C., and the time of the second curing treatment is 4-8 hours.

4. The preparation method according to claim 1, characterized in that: The product after the second solidification treatment is crushed, and the mesh size of the crushing treatment is 100 mesh to 325 mesh.

5. The preparation method according to claim 1, characterized in that: In the product obtained by the pre-carbonization, the lateral length La of the crystallite is 7 to 15 nm; Preferably, in the product obtained by the pre-carbonization, the mass proportion of oxygen element is 3% to 10%; Preferably, the pre-carbonization temperature is 300-800° C., and the pre-carbonization time is 2-8 hours.

6. The preparation method according to claim 1, characterized in that: The temperature of the high-temperature carbonization is 1100-1600° C., and the time of the high-temperature carbonization is 2-8 hours.

7. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: The hard carbon precursor material is sequentially subjected to a first curing treatment at 100 to 120° C. and a second curing treatment at 120 to 180° C., wherein the temperature of the first curing treatment is lower than the temperature of the second curing treatment, and the product after the second curing treatment is crushed at 100 to 325 meshes to obtain a cured resin product; Under a protective atmosphere, pre-carbonization is performed at 300 to 800° C., and in the pre-carbonized product, the lateral length La of the microcrystal is 7 to 15 nm, and the mass proportion of the oxygen element is 3% to 10%; The pre-carbonized product is subjected to high temperature carbonization at 1100-1600° C. to obtain a resin-based hard carbon material with a closed-cell structure; Wherein, the hard carbon precursor material comprises phenolic resin and hexamethylenetetramine, and the mass proportion of the hexamethylenetetramine in the hard carbon precursor material is 8% to 12%.

8. A resin-based hard carbon material, characterized in that: The resin-based hard carbon material is prepared by the preparation method according to any one of claims 1 to 7; The resin-based hard carbon material has a closed-pore structure inside.

9. A battery, characterized in that: The battery comprises the resin-based hard carbon material according to claim 8.

10. The battery according to claim 9, characterized in that The battery comprises a sodium ion battery.

Citation Information

Patent Citations

  • Asphalt resin-based hard carbon negative electrode material and preparation method thereof

    CN117550581A

  • Resin-based hard carbon material as well as preparation method and application thereof

    CN117963879A

  • Hard carbon material, preparation method thereof and sodium ion battery

    CN118572108A